COMPARATIVE STUDY OF INNER AND OUTER ROTOR FLUX REVERSAL PERMANENT MAGNET MACHINE FOR DIRECT DRIVE WIND TURBINE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
The topology, operation principle, and electromagnetic performance of the inner rotor flux reversal permanent magnet (IRFRPM) machine and the outer rotor flux reversal permanent magnet (ORFRPM) machine are quantitatively compared in this paper. First, the mass torque of both machines is optimized and compared using particle swarm optimization (PSO) combined with the finite element method (FEM). Second, the static properties of both machines are calculated using finite element analysis (FEA). Both machines are suitable for direct-drive wind turbines, but ORFRPM outperforms IRFRPM.
Keywords: Flux reversal machine; Outer rotor; Inner rotor; Direct drive; Wind turbine; Particle Swarm Optimzation; Computer-aided design